2013
DOI: 10.1111/adj.12109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of a herbal dentifrice on dentinal hypersensitivity: a randomized controlled clinical trial

Abstract: Background: Dentinal hypersensitivity is a common problem and there is a growing interest in herbal based formulations for the treatment of oral diseases. This study was conducted to assess the efficacy of a commercially available novel herbal dentifrice in reduction of dentinal hypersensitivity. Methods: A total of 73 subjects (38 males and 35 females; aged 25-60 years) were randomly divided into two groups: Group 1 -a placebo dentifrice (The Himalaya Drug Company Research and Development, Makali, Bangalore) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
0
22
0
3
Order By: Relevance
“…In vitro studies have shown that the Spinacia oleracia agent is effective in the occlusion of dentinal tubules through the formation of calcium oxalate crystals. In this review, three studies were included that refer to a statistical improvement in DH with the use of herbal dentifrices, two of which refer to the agent Spinacia oleracea . However, the presence of potassium nitrate in the composition of the described dentifrices does not allow a correct understanding of the true nature of the desensitising effect of Spinacia oleracia in the treatment of DH, since this effect may be due to the nitrate in the composition of the product.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that the Spinacia oleracia agent is effective in the occlusion of dentinal tubules through the formation of calcium oxalate crystals. In this review, three studies were included that refer to a statistical improvement in DH with the use of herbal dentifrices, two of which refer to the agent Spinacia oleracea . However, the presence of potassium nitrate in the composition of the described dentifrices does not allow a correct understanding of the true nature of the desensitising effect of Spinacia oleracia in the treatment of DH, since this effect may be due to the nitrate in the composition of the product.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a los agentes testeados encontramos (Gráfico 1): arginina, nitrato de potasio, fluoruro de potasio y de amina, citrato de potasio, oxalato de potasio, acetato de estroncio, nano hidroxiapatita, y fosfosilicato de calcio y sodio (CSPS) más conocido como Novamin ® (GlaxoSmithKline Consumer Healthcare, Weybridge, Surrey, Reino Unido). Las sales de potasio fueron las más investigadas, siendo 19 ensayos los que evaluaron alguna de sus formas (14,(16)(17)(18)(19)(20)25,26,28,29,(32)(33)(34)(35)(36)(37)(38)40,41) . De ellas, el agente más testeado fue el nitrato de potasio, 15 estudios evaluaron su eficacia; dos de ellos en colutorios (14,18) , uno en una combinación de colutorio y dentífrico (19) , y 12 en dentífricos al 5% (25,28,29,33,(35)(36)(37)(38)(39)(40)(41) .…”
Section: Resultsunclassified
“…In vitro studies have shown that phytocomplexes derived from rhubarb stalks ( Rhubarb rhaponicum ) and spinach leaves ( Spinacia oleracia ) are effective in occluding dentinal tubules through the formation of calcium oxalate crystals, and should be effective for the topical treatment of DH . In our previous preliminary study, a herbal‐based dentifrice containing potassium nitrate and Spinacia oleracia was found to be effective in the treatment of DH, as compared to the placebo group . However no positive control was used in our previous study.…”
Section: Introductionmentioning
confidence: 94%
“…17 In our previous preliminary study, a herbal-based dentifrice containing potassium nitrate and Spinacia oleracia was found to be effective in the treatment of DH, as compared to the placebo group. 18 However no positive control was used in our previous study.…”
Section: Introductionmentioning
confidence: 99%